2021
DOI: 10.1038/s41598-021-84663-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs modulate ethylene induced retrograde signal for rice endosperm starch biosynthesis by default expression of transcriptome

Abstract: Control of stage specific spike in ethylene production at anthesis has been a vauable route to potentially enhance genetic ceiling for grain filling of rice spikelet. A number of genes controlling ethylene homeostasis and starch synthesis have been identified so long, but lack of credible information on master modulation of gene expression by miRNAs and their target genes associated with hormonal dynamics obfuscate mechanisms controlling genotype difference in quantum of grain filling. The confusion accounts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In general, the spatial and temporal regulation of miRNAs varies between different tissues or organs of rice [39][40][41]. Thus far, a few studies have analyzed miRNAs in rice developing grains [42][43][44], while other studies used entire spikelets [45,46]. In this study, we specifically used caryopsis tissue from the R6 stage, which is defined as "the grain depth expansion stage at which milky starch in the developing grain is beginning to become firm but is still soft" [47], for analyzing miRNAs regulated by HDT.…”
Section: Identification Of Novel Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the spatial and temporal regulation of miRNAs varies between different tissues or organs of rice [39][40][41]. Thus far, a few studies have analyzed miRNAs in rice developing grains [42][43][44], while other studies used entire spikelets [45,46]. In this study, we specifically used caryopsis tissue from the R6 stage, which is defined as "the grain depth expansion stage at which milky starch in the developing grain is beginning to become firm but is still soft" [47], for analyzing miRNAs regulated by HDT.…”
Section: Identification Of Novel Mirnasmentioning
confidence: 99%
“…This is especially notable for Osa-miR1855, which was not detected in LaGrue at all. Osa-miR1846, which has been found to be highly expressed during grain filling in the spikelets [46], has been shown to target a heat shock factor (HSF) [96]. HSFs may induce chalkiness by promoting heat shock protein (HSP) expression [8,97].…”
Section: Microrna Profiles Differed Between Genetically Closely Relat...mentioning
confidence: 99%
“…Such differential expressions influenced the transcript abundance of MYB , MADS -box, GRF , ARF , and the Brassinosteroid insensitive 1 -associated receptor kinase 1 precursor ( BAK1 ), regulating various aspects of grain filling and development ( Zhu et al, 2008 ; Xue et al, 2009 ; Peng et al, 2013 ; Yi et al, 2013 ). Later on, the differential expressions of miRNAs in the spikelets based on their spatial locations have also been studied in order to throw light on the possible influence of miRNAs in differential grain filling in the superior and inferior spikelets of compact and heavy panicles ( Peng et al, 2011 ; Peng et al, 2014 ; Chandra et al, 2021 ; Panigrahi et al, 2021 ; Teng et al, 2021 ). These studies revealed that several miRNAs, including miR164/miR167, miR159, miR1861, and miR396h targeting auxin-responsive factor ARF8 , MYB , beta-amylase, and auxin efflux carrier protein, respectively, were expressed higher in the poorly filled inferior spikelets compared with the well-filled superior spikelets, indicating negative regulatory role of these miRNAs in grain filling.…”
Section: Regulation Of Grain Filling and Panicle Morphologymentioning
confidence: 99%
“…Thus, the role of miRNAs in corm development and starch and sucrose metabolism could be expected. This expectation is based on the earlier report in cassava that miRNAs effect the expression of genes involved in plant development, starch biosynthesis, and responses to the environmental stresses ( Panigrahi et al, 2021 ). Since, CircRNAs act as miRNA sponge to regulate target gene expression by inhibiting miRNA activity.…”
Section: Introductionmentioning
confidence: 99%